Early Weight Gain during Pregnancy: Which Women are the Most Affected? - Tebbani Fouzia; Oulamara Hayet; Agli Abdenacer (International Journal of Public Health Science (IJPHS), 2016)
Maternal weight gain during pregnancy is a good prediction tool in short and long term health of pregnant women and their children. To study the effect of early weight gain of pregnant women until the end of the 2nd trimester of pregnancy, depending on their pre-pregnancy body mass index. 116 healthy pregnant women were followed until the 2nd trimester of pregnancy, their weight and height before pregnancy, as well as the current weight at the end of the 1st and 2nd trimesters were collected. Data included age, parity, eating habits and physical activity level. Statistics were performed using the Statview software. The mean pre-pregnancy BMI was 27 ± 5.27 kg/m². Weight gain in the 2nd trimester is 6.33 ± 4.84 kg. It decreases with the increasing age of the mother (25% of women between 20 and 24.9 years vs 12.5% of more than 35). Also, it decreases with the increasing number of children (62.5% in nulliparous vs 25% in multiparous). Breakfast is skipped by 64.5 % of overweight pregnant women in the 1st trimester and 90 % in the 2nd one. 80.17% and 69.83% of pregnant women do not practice any physical activity. Overweight and obese pregnant women before pregnancy do not take enough weight during pregnancy. Prospects will to analyze behaviors related to health and social status.